Miniaturized SAW convolver for indoor mobile communication - Fauter, Andreas; Reindl, Leonhard; Weigel, Robert; Russer, Peter; Seifert, Franz (IEEE Ultrasonics Symposium, 1993)
Design and performance of a miniaturized prototype SAW convolver on YZ-LiNbO3 are reported. The small and compact device fits into an SMD package of size 18×8.2×2.4 mm3. Output summing is realized with two bond wires, and external matching circuitry incorporates only simple lumped elements such as SMD components and copper coils. At a center frequency of 350 MHz, an integration time of 3 μs and a bandwidth of 50 MHz, i.e. a time-bandwidth product of 150, have been obtained. The achieved efficiency of -70 dBm±0.5 dB may be improved considerably. The deviation from linear phase was less than ±50. Uniformity and corresponding phase were within ±0.5 dB and ±50, respectively
elib2cris::1512001600,fauter1993